The new feminist frontier on community-based learning - Rita Basílio Simões; Inês Amaral; Sofia José Santos (European Journal for Research on the Education and Learning of Adults, 2021)
Feminist activism has always promoted informal learning opportunities for men and women. Internet, along with ICTs have expanded these opportunities by affording large-scale feminist mobilising and connection. Yet the digital environment is not only enhancing feminist campaigning but also facilitating the contexts to abusive behaviours flourish. Departing from the concept of social movement learning, in this article, we examine the significance to adult education of the large-scale reinvigoration of feminist activism in tandem with the surge of anti-feminist and misogynist ideas in the digital environment. We argue that just as online social media brought unprecedented opportunities to provide social movement learning, it offered the same tools to misogynists groups, mostly led by a toxic understanding of masculinity. By co-opting the same online opportunities, the feminist movement enjoys, individualised and collective toxic masculinity agency is a potential foe to match, reinventing the same struggle, demanding an ongoing battle towards deconstructing patriarchy.